Challenges for Professional Development of Malaysian ESL Teachers - Omar, Ruzana; Ab. Rashid2, Radzuwan (KnE Social Sciences, 2019)
The paper aims to provide insights into the current understanding of the challenges faced by in-serviced primary school ESL teachers in completing their degree on a part-time basis. In relation to the government’s effort to improve the quality of primary education, many English language teachers have enrolled in the ‘Teacher’s First-degree program’ offered by the Ministry of Education. The participants of the program, somehow, face a number of challenges. As adult learners, the ESL teachers need to follow in doing the degree part time as all of them are full time teachers and teaching in different schools. Sociocultural theory of Lev Vygotsky provided the theoretical framework for this case study. This qualitative study explored the experiences of five in-service primary school English language teachers who were involved in the program. Semi-structured interviews were carried out to identify the challenges faced by the teachers in completing a primary school teacher’s first-degree program organized by the Ministry of Education (MOE). The main data generated from semi-structured interviews was analysed using thematic analysis approach. The findings revealed that job commitments, family commitments, health mental issue and time management are the main challenges faced by them. Exploring in-service primary school English teachers challenges in furthering their studies part-timely might give the Ministry of Education (MOE) consideration in understanding of language teachers’ selves and needs while pursuing their first degree. This research might also be helpful to investigate the current practices of the professional development of primary school English teachers in Malaysia. Keywords: ESL teacher, teacher professional development, part-time degree, inservice teacher, challenges